3-Nitro-2(1H)-quinolone derivatives as 2π components in 1, 3-dipolar cycloadditions of azomethine ylides: A new synthesis of pyrrolo[3, 4-c]quinolines. Issue 1 (2nd January 2023) - Molnár, Márk; John, Tamás; Dancsó, András; Nyerges, Miklós
Abstract: The 1, 3-dipolar cycloaddition of 3-nitro-2(1 H )-quinolones with ester-stabilized azomethine ylides derived from sarcosine ester and various aromatic aldehydes has been investigated. The structure and stereochemistry of cycloadducts were studied in detail by X-ray and NMR spectroscopy methods. GRAPHICAL ABSTRACT: UF0001